Development of a red absorbing Se-rhodamine photosensitizer and its application for bio-orthogonally activatable photodynamic therapy. Issue 49 (30th May 2019) - Lv, Weijie; Chi, Siyu; Feng, Wenqi; Liang, Tao; Song, Dan; Liu, Zhihong
Abstract : A π-extended Se-rhodamine was employed for the construction of a bio-orthogonally activatable photosensitizer. Abstract : A π-extended red absorbing Se-rhodamine (Se-NR ) was synthesised and characterized. By masking the amine ofSe-NR as an azide, we successfully constructed a bio-orthogonally activatable photosensitizer (Se-NR-Az ).Se-NR-Az was not photocytotoxic, but when activated by the Staudinger reaction, photocytotoxicity was restored.